Bioaugmented constructed wetlands for efficient saline wastewater treatment with multiple denitrification pathways. (September 2021) - Zhao, Lin; Fu, Guiping; Wu, Jinfa; Pang, Weicheng; Hu, Zhangli
Graphical abstract: Highlights: 1. Nitrogen removal efficiency was improved by adding Zobellella sp. A63. 2. Ammonia-oxidizing archaea, Nitrosomonas, Nitrospira ensure effective nitrification. 3. High and low C/N benefit aerobic and sulfur-driven denitrifiers, respectively. 4. Nitrogen was mainly removed by aerobic and sulfur autotrophic denitrification. 5. Bioaugmentation and carbon-source regulation were crucial for the denitrification. Abstract: Six laboratory-scale constructed wetlands (CWs) were used to quantify the nitrogen removal (NR) capacity in the treatment of saline wastewater at high (6:1) and low (2:1) carbon–nitrogen ratios (C/N), with and without bioaugmentation of aerobic-denitrifying bacterium. Sustained high-efficiency nitrification was observed throughout the operation. However, under different C/N ratios, although the bioaugmentation of aerobic-denitrifying bacterium promoted the removal of NO3 – –N and TN, there were still great differences in denitrification. Molecular biology experiments revealed ammonia-oxidizing archaea, together with the Nitrosomonas and Nitrospira, led to highly efficient nitrification. Furthermore, aerobic-denitrifying bacterium and sulfur-driven denitrifiers were the core denitrification groups in CWs. By performing these combined experiments, it was possible to determine the optimal CW design and the most relevant NR processes for the treatment of salty wastewater. The results suggest that the bioaugmentation of salt-tolerant functional bacteria with multiple NR pathways are crucial for the removal of salty wastewater pollutants.